1988
DOI: 10.1038/334248a0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of mutation causing Friedreich's ataxia to human chromosome 9

Abstract: Friedreich's ataxia is an autosomal recessive disease with progressive degeneration of the central and peripheral nervous system. The biochemical abnormality underlying the disorder has not been identified. Prompted by the success in localizing the mutations causing Duchenne muscular dystrophy, Huntington's disease and cystic fibrosis, we have undertaken molecular genetic linkage studies to determine the chromosomal site of the Friedreich's ataxia mutation as an initial step towards the isolation and character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
93
0
6

Year Published

1990
1990
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(102 citation statements)
references
References 21 publications
0
93
0
6
Order By: Relevance
“…Therefore, efforts to understand the disorder are directed towards isolating the disease gene on the basis of its genomic map position. Chamberlain et al (4) mapped the FA gene (FRDA in the Human Gene Mapping Workshop nomenclature) to chromosome 9 by virtue of its tight linkage to the polymorphic locus D9S15 (probe pMCT112). We confirmed this linkage in another set of families and identified a second closely linked marker locus, D9S5 (5).…”
mentioning
confidence: 99%
“…Therefore, efforts to understand the disorder are directed towards isolating the disease gene on the basis of its genomic map position. Chamberlain et al (4) mapped the FA gene (FRDA in the Human Gene Mapping Workshop nomenclature) to chromosome 9 by virtue of its tight linkage to the polymorphic locus D9S15 (probe pMCT112). We confirmed this linkage in another set of families and identified a second closely linked marker locus, D9S5 (5).…”
mentioning
confidence: 99%
“…Clinical diagnostic criteria for typical cases basically include: a) early age of onset < 20 16 or 25 years 17 , b) autosomal recessive inheritance, c) progressive ataxia of limbs and gait, and d) absence of lower limb tendon reflexes. Chamberlain et al (1988) 8 mapped the Friedreich's ataxia gene to chromosome 9, which was subsequently confirmed 15 . Later, recombinant events 3 allowed the successive narrowing of the candidate region 7,10,22,26 .…”
mentioning
confidence: 76%
“…1,10,11) The hypothesis that FRDA is due to accumulation of mitochondrial iron leading to increased production of free radicals impairing the mitochondria and cell functions was more directly evidenced by Delatycki, et al 10,[12][13][14][15] Studies have reported a relationship between the number of GAA repeats in the smaller frataxin allele and cardiomyopathy in about two-thirds of patients homozygous for the GAA expansion. [16][17][18] Isnard, et al showed that the severity of left ventricular hypertrophy was related to the number of GAA repeats.…”
Section: Discussionmentioning
confidence: 99%